The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/mi12111336
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering Meets Nanotechnology: Molecular Mechanism Modulations in Cornea Regeneration

Abstract: Nowadays, tissue engineering is one of the most promising approaches for the regeneration of various tissues and organs, including the cornea. However, the inability of biomaterial scaffolds to successfully integrate into the environment of surrounding tissues is one of the main challenges that sufficiently limits the restoration of damaged corneal tissues. Thus, the modulation of molecular and cellular mechanisms is important and necessary for successful graft integration and long-term survival. The dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Combining an ECM scaffold with nanoparticles (NPs) can promote targeted and controlled drug release and improve the bioavailability and biodistribution of therapeutic molecules [ 128 , 129 , 130 ]. An in vivo study on Parkinson’s disease drug delivery showed that the intracranial implantation of scaffolds embedded with dopamine-loaded cellulose acetate phthalate nanoparticles resulted in sustained drug delivery.…”
Section: Applications Of Ecm Scaffolds From Other Sources In Tissue E...mentioning
confidence: 99%
See 3 more Smart Citations
“…Combining an ECM scaffold with nanoparticles (NPs) can promote targeted and controlled drug release and improve the bioavailability and biodistribution of therapeutic molecules [ 128 , 129 , 130 ]. An in vivo study on Parkinson’s disease drug delivery showed that the intracranial implantation of scaffolds embedded with dopamine-loaded cellulose acetate phthalate nanoparticles resulted in sustained drug delivery.…”
Section: Applications Of Ecm Scaffolds From Other Sources In Tissue E...mentioning
confidence: 99%
“…Some limitations of tissue-engineered corneal transplants are suboptimal integration and the risk of tissue rejection, especially in the case of treating acutely damaged and highly inflamed tissues [ 37 , 182 ]. Poor interactions between the graft and host tissue could influence multiple molecular events, including healing, inflammation, ECM remodeling, and cell death at the graft host site [ 16 , 129 , 183 ]. Corneal scaffold fabrication with nanomaterials has the potential to improve the physicochemical properties that enhance graft integration in the host tissue [ 129 ].…”
Section: Perspective On Translating Existing Knowledge Of Ecm-based S...mentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular and cellular modulation indeed is important and necessary for successful graft integration, post-surgery clinical outcome and long-term survival. The authors specifically addressed corneal tissue engineering, which has attracted great interest recently, due to the attempts to avoid many of the complications encountered in traditional donor corneal transplantation [5]. The involvement of cells could not only allow the creation of a cornea analog, which should provide high optical transparency, mechanical integrity and proper cell behavior, leading to effective re-epithelialization, but also give promises for the full regeneration and integration of the graft.…”
mentioning
confidence: 99%